Construction of a Transcription Map for Papillomaviruses using RACE, RNase Protection, and Primer Extension Assays. Issue 1 (8th February 2016) - Wang, Xiaohong; Zheng, Zhi‐Ming
Abstract: Papillomaviruses are a family of small, non‐enveloped DNA tumor viruses. Knowing a complete transcription map of each papillomavirus genome can provide guidance for various papillomavirus studies. This unit provides detailed protocols to construct a transcription map of human papillomavirus type 18. The same approach can be easily adapted to other transcription map studies of any other papillomavirus genotype due to the high degree of conservation in genome structure, organization, and gene expression among papillomaviruses. The focused methods are 5′‐ and 3′‐rapid amplification of cDNA ends (RACE), which are techniques commonly used in molecular biology to obtain full‐length RNA transcript or to map a transcription start site (TSS) or an RNA polyadenylation (pA) cleavage site. Primer walking RT‐PCR is a method for studying the splicing junction of RACE products. In addition, RNase protection assay and primer extension are also introduced as alternative methods in the mapping analysis. © 2016 by John Wiley & Sons, Inc.